Exploration and practice of an inter-embedded engineering excellence talent cultivation mechanism with three dimensions and six stages - Wang, Caidong; Xiao, Yanqiu; Xiao, Zhiling; Li, Li; Pan, Xueli (Frontiers in Education, 2025)
To implement the concept of “Student-Centered, Outcome-Based Education, and Continuous Quality Improvement” engineering education, exploring the establishment and implementation of an inter-embedded mechanism between innovation and entrepreneurship education (dual-creation) and engineering education. This study is based on the teaching reform practices of Zhengzhou University of Light Industry. It proposes a “three dimensions-six stages” inter-embedded cultivation mechanism using case studies, questionnaires, and comparative analysis. The mechanism is built on six phases: Cultivation Program Revision, Curriculum System Reform, Teaching Method Matching, Practice Teaching Optimization, Teaching Research Feedback, and Industry-Teaching Integration with Continuous Improvement. A quality evaluation function for the teaching team has been established. After research and data analysis, the results show that the distribution of professional titles among our school’s innovative teacher team follows a normal distribution from junior to senior levels. The comprehensive quality evaluation score is 82.68, which is in the good category. It consists of the university’s emphasis on innovation and entrepreneurship education. Student feedback indicates a lack of proficiency in solving complex engineering problems. It necessitates continuous improvement and optimization of the inter-embedded teaching system.